A Case Report of Well-Differentiated Liposarcoma Presenting as a Primary Inguinal Mass: Diagnostic Challenges and Management - Komang Budhi Pradnya Wibawa; Gede Bayu Wedanta Netra (The International Journal of Medical Science and Health Research, 2025)
Introduction: Liposarcoma (LPS) is the most common soft tissue sarcoma in adults, yet its presentation as a primary mass in the inguinal region is exceedingly rare. This atypical location poses a significant diagnostic challenge, as the clinical signs often mimic more common benign conditions such as inguinal hernia or lipoma, which can lead to delayed diagnosis or inadequate initial management. This report details a case of well-differentiated liposarcoma (WDLS) in the inguinal canal, highlighting the clinical, radiological, and pathological nuances critical for accurate diagnosis and definitive treatment. Case Illustration: A 49-year-old male presented with a one-month history of a right inguinal lump that had rapidly enlarged over the preceding week, accompanied by intermittent pain. Physical examination revealed a mobile, tender mass measuring approximately 2x3 cm. Ultrasound imaging was pivotal, identifying a solid, heterogeneous, vascularized lesion, which raised the suspicion of a neoplasm beyond a simple lipoma. The patient subsequently underwent a wide excisional biopsy.Histopathological examination revealed a tumor composed of mature adipocytes with scattered atypical, hyperchromatic stromal cells and neoplastic lipoblasts, confirming the diagnosis of well-differentiated liposarcoma. A notable and potentially misleading feature was the presence of a prominent "chicken wire" vascular pattern within the stroma, a finding more classically associated with myxoid liposarcoma.1 Discussion: This case underscores the importance of maintaining a high index of suspicion for malignancy in patients presenting with atypical inguinal masses. Preoperative imaging, particularly ultrasound with Doppler, is invaluable for identifying features suggestive of sarcoma, thereby guiding appropriate surgical planning toward a wide excision rather than a simple enucleation. The finding of a "chicken wire" vascular pattern within a WDLS represents a significant diagnostic pitfall, emphasizing the need for comprehensive morphological assessment and, in equivocal cases, ancillary molecular testing to avoid misclassification and subsequent inappropriate adjuvant therapy. Wide surgical excision with negative margins remains the cornerstone of treatment for localized WDLS. Conclusion: Well-differentiated liposarcoma is an essential, albeit rare, differential diagnosis for solid inguinal masses. Optimal patient outcomes are contingent on a multidisciplinary approach encompassing astute clinical suspicion, appropriate imaging, meticulous pathological evaluation, and definitive surgical management. Given the high risk of local recurrence and the potential for dedifferentiation into a more aggressive sarcoma, a structured protocol of long-term, lifelong surveillance is mandatory following initial treatment. Keywords: Liposarcoma, Well-Differentiated Liposarcoma, Inguinal Tumor, Spermatic Cord, Soft Tissue Sarcoma.